Experimental Study of Measuring the Wrinkle of Solar Sails - Jie Zou; Dongxu Li; Jie Wang; Ye Yu (Aerospace, 2022)
Conducting a wrinkling analysis for a membrane structure of complex boundary conditions is quite difficult. This paper develops a numerical calculation method for completing a wrinkling analysis of a square membrane structure and a trapezoidal membrane structure with static corner forces. Furthermore, an experimental system for measuring the wrinkle is designed and established to verify the correctness of the method. The difference between simulation analysis results and experimental results is quite small for small corner forces, which means the method used for the wrinkling analysis under small loads is effective.